Sustainable crops of wild agaves from Jalisco for the production of raicilla - Sánchez-González, Dolores Javier (Revista Mexicana de Ciencias Agrícolas, 2025)
This study aimed to analyze the sustainable cultivation and conservation of raicillero agaves since 2022, highlighting their role in the preservation of biodiversity in the raicilla industry. The central problem lies in the pressure on local ecosystems due to the increase in international demand for the distillate, which threatens the genetic diversity of the agave species used. Through a census methodology based on interviews, exhaustive documentary analysis, and statistical data, sustainable agricultural practices, such as the reforestation of wild agaves, and micropropagation techniques were identified in the 17 municipalities with the raicilla designation of origin; 16 in Jalisco: Atengo, Chiquilistlán, Juchitlán, Tecolotlán, Tenamaxtlán, Puerto Vallarta, Cabo Corrientes, Tomatlán, Atenguillo, Ayutla, Cuautla, Guachinango, Mascota, Mixtlán, San Sebastián del Oeste, and Talpa de Allende and 1 in Nayarit: Bahía de Banderas. The results indicate that Agave maximiliana Baker continues to dominate the cultivation for raicilla, which represents 75.4% of the current plantations, whereas Agave angustifolia Haw. and A. inaequidens have significant increases in adoption, reaching shares of 31.6% and 7%, respectively. It was concluded that it is essential to continue with the reforestation of agaves, implement public policies, sustainable certifications, and technological innovation to strengthen their competitiveness in international markets and ensure their contribution to rural development and environmental conservation in Mexico.